PENGARUH WAKTU BLANCHING DAN SUHU PENGERINGAN PADA PEMBUATAN TEPUNG BEKATUL - satria perdana, Deni; Muchsiri, Mukhtarudin (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2014)
This study aims to determine the moisture content, ash and carbohydrates bran flour blancing instant of time and the effect of drying temperature and determine the sensory characteristics of rice bran flour blancing instant of time and the effect of drying temperature. This study was conducted in laboratory of the Faculty of Agriculture, University of Muhammadiyah Palembang in July 2013 until December 2013. This study used a randomized block design (RBD) consisting of two factors, namely the treatment of blanching time and drying temperature and each made into a three-level treatment factor with nine treatment combinations were repeated three times. Parameters observed in this study is the chemical analysis includes analysis of carbohydrate content, ash content and moisture content. While the organoleptic tests include scents and colors using the friedman test (hendonik) . Effect of blanching time and temperature Drying On Making Wheat Bran Instant significant effect on levels of carbohydrates , moisture content and ash content of instant rice bran flour. Water content was highest in the treatment of B3 (blanching 15 minutes) with an average value of 7.436%, the highest ash content present in the B3 treatment (blanching 15 minutes) with an average value of 6.109% and carbohydrate content of instant rice bran flour was highest in treatment B3 (blanching 15 minutes) with an average value of 64.740%. Sensory test for color and aroma , the highest level of the color preferences of instant rice bran flour contained on B1S1 treatment interaction (5 min blanching time and drying temperature of 500C) with an average value of 4.25 (preferred criteria) and the highest level of joy to the aroma of rice bran flour instant contained on B1S1 treatment interaction (5 min blanching time and drying temperature 500C) with an average value of 3.83 (rather preferred criteria). 97.5 %). To get a good instant rice bran flour authors suggest you should use B1S1 treatment.